Coupling PAF signaling to dynein regulation: structure of LIS1 in complex with PAF-acetylhydrolase. - Tarricone, C; Perrina, F; Monzani, S; Massimiliano, L; Kim, M; Derewenda, Z; Knapp, S; Tsai, L; Musacchio, A (2004)
Mutations in the LIS1 gene cause lissencephaly, a human neuronal migration disorder. LIS1 binds dynein and the dynein-associated proteins Nde1 (formerly known as NudE), Ndel1 (formerly known as NUDEL), and CLIP-170, as well as the catalytic alpha dimers of brain cytosolic platelet activating factor acetylhydrolase (PAF-AH). The mechanism coupling the two diverse regulatory pathways remains unknown. We report the structure of LIS1 in complex with the alpha2/alpha2 PAF-AH homodimer. One LIS1 homodimer binds symmetrically to one alpha2/alpha2 homodimer via the highly conserved top faces of the LIS1 beta propellers. The same surface of LIS1 contains sites of mutations causing lissencephaly and overlaps with a putative dynein binding surface. Ndel1 competes with the alpha2/alpha2 homodimer for LIS1, but the interaction is complex and requires both the N- and C-terminal domains of LIS1. Our data suggest that the LIS1 molecule undergoes major conformational rearrangement when switching from a complex with the acetylhydrolase to the one with Ndel1.